PARTISIPASI POLITIK MASYARAKAT ETNIS TIONGHOA DI KECAMATAN LUBUK BAJA DALAM PEMILIHAN WALIKOTA KOTA BATAM TAHUN 2015 - Arini Ameswari; Mita Rosaliza (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The difficult time that happened during New Order for Chinese ethnics in political world caused their political participation is classified low this time so they choose to involve economically. By the end of the New Order, little by little the discrimination that they have felt finally started to be distinguished with the appearance of policies to stop the usage of terms such as Pribumi (indigenous) and Non-Pribumi (non-indigenous) to every aspect, including politic. It started to change Chinese ethnics’ attitude towards political activities. This research was conducted in Lubuk Baja District, Batam City. The purpose of this research is to describe political participation of Chinese ethnics in Mayor Election of Batam City in 2015, using rational choice theory. The researcher uses descriptive qualitative method with data collection technique by interviewing and documenting. Purposive sampling is used as sampling technique with the subject of the research includes key informants and 5 informants from Chinese ethnics. The result of this research shows that citizens with Chinese ethnicity in Lubuk Baja District, Batam City are still classified as a non-rational choicer for political participation even though politics around Chinese ethnics have developed this time. Other than that, there are internal and external factors that influenced them to participate in politic. Those internal factors are the less care of the citizens to participate in politic, they do not like to intervene other people’s business and thought that politic is hassling. Meanwhile the external is the environment around them, such as their housing.Keywords: Political participation, Chinese ethnics, Mayor election, Lubuk Baja district